Developing growth mindsets : principles and practices for maximizing students' potential - Wilson, Donna (Psychologist); Conyers, Marcus (ASCD, 2020)
"This hands-on, practical book explains the brain research behind the concept of mindset, explores the connections to student engagement and achievement, and shows teachers how to develop positive mindsets-for themselves and in their classrooms"--